Infant and young child feeding practices and nutritional status in Bhutan. Issue 3 (21st December 2017) - Campbell, Rebecca K.; Aguayo, Victor M.; Kang, Yunhee; Dzed, Laigden; Joshi, Vandana; Waid, Jillian; Gupta, Suvadra Datta; Haselow, Nancy; West, Keith P.
Abstract: In South Asia, childhood undernutrition persists while overweight is increasing. Internationally recommended infant and young child feeding (IYCF) practices promote healthy nutritional status; however, little is known about IYCF in Bhutan, investigated here using 2015 National Nutrition Survey data. WHO/UNICEF IYCF indicators, anthropometry and household socio‐economic status were available for 441 children <24 months. Stunting, wasting, and underweight prevalence (<−2Z length‐for‐age [LAZ], weight‐for‐age, [WAZ] and weight‐for‐length [WLZ], respectively) were 15%, 9%, and 5%, respectively, whereas overweight (WLZ >2) prevalence was 6%. In survey‐design‐adjusted analyses, 52% of mothers of 0‐ to 5‐month olds reported exclusive breastfeeding (EBF), with EBF less common for girls than boys (OR: 0.2 [95% CI: 0.1–0.9]). Although 61% of children were breastfed at 2 years and 75% of children >6 months met a minimum daily meal frequency, only 18% of children 6–23 months met minimum dietary diversity. IYCF was unassociated with risk of stunting, wasting, or underweight, possibly due to relatively low prevalence of anthropometric failure and small sample size. However, currently‐breastfed children were less often overweight [OR: 0.1 (95% upper limit ≤1.0)]. Neither breastfeeding nor most complementary feeding practices differed by socio‐economic status, but children in the highest two fifth of a wealth index had 7.8 (1.3–46.9) and 5.3 (1.1–25.2) times greater odds than children in the lowest fifth of meeting minimum dietary diversity criteria. Low rates of EBF, given possible protection of breastfeeding against overweight, and inadequate dietary diversity offer evidence to guide future program interventions to improve nutritional status of young children.